Simulation of local thinned the inner surface of the pipelin for construction of stress state near defect - Шугайло, О.П.; Крицький, В.Б.; Луговий, П.З. (Proceedings of National Aviation University (archive), 2006)
The models of a defect-thinning of pipes fragment as an ellipse, elliptic paraboloid and elliptic cone are developed in order to analyze their impact on a stress state of a construction at the defect zone.